Crystallization behavior of poly(ethylene terephthalate‐co‐neopentyl terephthalate‐co‐ethylene isophthalate‐co‐neopentyl isophthalate) copolyester and its application in laminated tin‐free steel. Issue 31 (8th May 2015) - Ding, Liping; Xie, Long; Cao, Jianyun; Bai, Yongping
ABSTRACT A low crystallinity, the copolyester poly(ethylene terephthalate‐co‐neopentyl terephthalate‐co‐ethylene isophthalate‐co‐neopentyl isophthalate) (PENIT) was synthesized and applied for laminated tin‐free steel. The structures and thermal properties of the copolyester were characterized by 1H‐NMR, thermogravimetry analysis, differential scanning calorimetry, wide‐angle X‐ray diffraction, and polarized optical microscopy. Differential scanning calorimetry, wide‐angle X‐ray diffraction, and polarized optical microscopy results show that the crystallization ability of the copolyester decreased obviously. Meanwhile, the peel strength, crystallinity, and water‐vapor permeability of the copolyester film were also measured at varied lamination temperatures. The result confirm that an improvement in the lamination temperature led to an increased ratio of amorphous PENIT to crystalline PENIT and decreased structural orientation, and the decrease in the structural orientation sped up the increase in the rate of water‐vapor permeability. On the basis of the purpose of reducing a detrimental effect on the corrosion resistance caused by water permeation, a reasonable lamination temperature was selected. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42308.